Karakter Api Sebagai Simbol Emosi Dalam Penciptaan Karya Seni Lukis - Rahditya, Ida Bagus Mas Putra; Mustika, I Ketut; Putra, I Gede Jaya (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
This report contains a description of the creation of works of painting with the theme "Fire character as a symbol of an emotion in the creation of works of painting." This theme is inspired by the use of fire symbols to represent various emotions in art. In general, this report discusses how the symbol of fire can be used to depict emotions and characters in works of art. The problem faced is how to visualize emotions and characters through the symbol of fire to represent ideas, phenomena, meanings and techniques presented in creating works of painting. The creation method is a process of creating work systematically. In realizing this creation, the methods used include: basic research, exploration stages, experimentation, improvisation, and formation. The aim to be achieved in creatingthis work is to reveal how fire as a symbol of emotion can be a medium for creativity and imagination in the form of paintings, by applying the principles of fine art to create six works during this sixth semester.